2009
DOI: 10.1380/ejssnt.2009.259
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bi-Polaronic Ground State in K/Si(111):B

Abstract: We report here on low energy electron diffraction (LEED), Auger spectroscopy, scanning tunneling microscopy (STM) and angle-resolved photoemission (ARPES) studies of ultrathin films of K/Si(111)-√ 3 × √ 3R30:B. A potassium-induced surface state is evidenced being maximum at the saturation coverage. ARPES data clearly evidence the folding of the K-induced surface band near the expected kF attesting of a large Mott gap ∆ = 500 meV and a very narrow measured bandwidth W = 140 meV. This clearly signs the strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, the e–ph coupling (E p ) is very strong to give a negative U eff (= −0.79 eV), favoring the formation of a two-electron bound state. These U and E p values are, however, similar to those of potassium (K)-deposited √3 surface: Cardenas et al observed a strong temperature dependent Franck–Condon broadening of the occupied surface band of K-deposited √3-surface near −0.8 eV and, from the model fitting of such behavior, determined the e–ph coupling parameters, i.e., g 2 ≈ 8 and ℏω = 55 meV. These, in turn, give E p ≈ 0.44 eV and U ≈ 0.16 eV, being close to our values.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…On the other hand, the e–ph coupling (E p ) is very strong to give a negative U eff (= −0.79 eV), favoring the formation of a two-electron bound state. These U and E p values are, however, similar to those of potassium (K)-deposited √3 surface: Cardenas et al observed a strong temperature dependent Franck–Condon broadening of the occupied surface band of K-deposited √3-surface near −0.8 eV and, from the model fitting of such behavior, determined the e–ph coupling parameters, i.e., g 2 ≈ 8 and ℏω = 55 meV. These, in turn, give E p ≈ 0.44 eV and U ≈ 0.16 eV, being close to our values.…”
supporting
confidence: 90%
“…These, in turn, give E p ≈ 0.44 eV and U ≈ 0.16 eV, being close to our values. A similar e–ph coupling behavior between bare and K-deposited √3-surfaces may be ascribed to rather a simple role of potassium; that is, it transfers its 4s electrons to the √3-surface without significant interactions …”
mentioning
confidence: 81%
See 2 more Smart Citations